Studi Kelayakan Investasi Proyek Perumahan pada Proyek Pembangunan Perumahan Aura Tirta Graha Banjarnegara - Priyo, Mandiyo (Universitas Muhammadiyah Yogyakarta, 2012)
The aim of this study is to evaluate the cash flow and the feasibility of the building investment project of Perumahan Aura Tirta Graha Banjarnegara. The data used in this study were collected from the contractor. The collected data were classified into two groups: primary and secondary data. The primary data cover the direct detailed examination of the research objectives. The data were collected by doing interview and observation. On the other hand, the secondary data were the historic data dealing with the plan and implementation of the project. In this study, there were several methods carried out in measuring the criterion of investment feasibility, i.e.: Break Event Point (BEP), Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI).Â Evaluation results show that every method demonstrated various performance of the investment appropriateness. From the analysis, it can be concluded that the development plan of Perumahan Aura Tirta Graha Banjarnegara has been carefully analyzed and properly implemented.